2019
DOI: 10.1101/778746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A viral ring nuclease anti-CRISPR subverts type III CRISPR immunity

Abstract: The CRISPR system provides adaptive immunity against mobile genetic elements in bacteria and archaea. On detection of viral RNA, type III CRISPR systems generate a cyclic oligoadenylate (cOA) second messenger 1-3 , activating defence enzymes and sculpting a powerful antiviral response that can drive viruses to extinction 4,5 . Cyclic nucleotides are increasingly implicated as playing an important role in host-pathogen interactions 6,7 . Here, we identify a widespread new family of viral anti-CRISPR (Acr) enzym… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(86 citation statements)
references
References 59 publications
(44 reference statements)
3
83
0
Order By: Relevance
“…386 387 Crn3 has a highly unusual cooperative catalytic mechanism 388 A. fulgidus Crn3/Csx3 is a much faster enzyme than Crn1. The single turnover reaction rate for cA 4 389 cleavage of 3.6 min -1 is closer to that of the AcrIII-1 family, which utilise a distinct active site 390 architecture, employing a conserved histidine residue as a general acid to stabilise the oxyanion 391 leaving group (Athukoralage et al, 2020b). This raises an important question: why does Crn3/Csx3 392 degrade cA 4 so quickly when it plays a role in cellular defence rather than viral offense?…”
Section: Figure 6 Sigmoidal Response Of Ring Nuclease Activity As a mentioning
confidence: 88%
See 4 more Smart Citations
“…386 387 Crn3 has a highly unusual cooperative catalytic mechanism 388 A. fulgidus Crn3/Csx3 is a much faster enzyme than Crn1. The single turnover reaction rate for cA 4 389 cleavage of 3.6 min -1 is closer to that of the AcrIII-1 family, which utilise a distinct active site 390 architecture, employing a conserved histidine residue as a general acid to stabilise the oxyanion 391 leaving group (Athukoralage et al, 2020b). This raises an important question: why does Crn3/Csx3 392 degrade cA 4 so quickly when it plays a role in cellular defence rather than viral offense?…”
Section: Figure 6 Sigmoidal Response Of Ring Nuclease Activity As a mentioning
confidence: 88%
“…Each datapoint is the average of three technical replicates and error bars show the standard deviation of the mean. nuclease 2 (Crn2) enzymes (Athukoralage et al, 2020b, Samolygo et al, 2020 picture is becoming clearer for the specific ring nucleases as they are identified in different 382 archaeal and bacterial genomes (Figure 7). It appears to be an emerging paradigm that cells with a 383 type III CRISPR defence require a mechanism to remove the cOA signal, either once viral infection 384…”
Section: Figure 6 Sigmoidal Response Of Ring Nuclease Activity As a mentioning
confidence: 99%
See 3 more Smart Citations